Understanding Education and Educational Research - Smeyers, Paul; Smith, Richard (Cambridge : Cambridge University Press, 2014)
Educational research is widely believed to be essentially empirical, consisting mainly of collecting and analysing data, with randomised control trials as the'gold standard'. This book argues that good educational research is often philosophical in nature. Offering a critical overview of the current state of educational research, the authors argue that there are two factors in particular that distort it. One is that throughout the world it is expected to serve the interests of the state in securing educational improvements, as measured by standardised examination results, and to demonstrate'scientific' credentials sufficient to guarantee absence of ideological bias and carry conviction. The other is that learning to do educational research is generally seen as a matter of being trained in empirical'research methods'. The authors demonstrate, by contrast, that good educational research needs the rigorous thinking characteristic of philosophy, and that philosophical treatments themselves sometimes constitute such research.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).
Keywords: Education research